2011
DOI: 10.2741/3876
|View full text |Cite
|
Sign up to set email alerts
|

Applications of proteomics in cartilage biology and osteoarthritis research

Abstract: In osteoarthritis (OA) the turnover of extracellular matrix (ECM) macromolecules is disrupted by catabolic changes that lead to the production of a range of inflammatory mediators and the loss and fragmentation of proteoglycans, fibrillar and non-fibrillar collagens. These events result in the degradation and release of ECM fragments, which are potential biomarkers that can be detected in synovial fluid, blood and urine. Proteomics is increasingly applied in cartilage research and has the potential to advance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…5 An increasing number of studies have examined normal and OA articular cartilage, in humans and animals, to shed light on biology and composition of cartilage and the pathological processes leading to OA. [6][7][8][9] They suggest that the degradation and release of molecules from cartilage to body fluids varies according to status and severity of the pathological process. It has been shown that for example, the concentration of released cartilage oligomeric protein (COMP) may indicate the severity of the disease.…”
mentioning
confidence: 99%
“…5 An increasing number of studies have examined normal and OA articular cartilage, in humans and animals, to shed light on biology and composition of cartilage and the pathological processes leading to OA. [6][7][8][9] They suggest that the degradation and release of molecules from cartilage to body fluids varies according to status and severity of the pathological process. It has been shown that for example, the concentration of released cartilage oligomeric protein (COMP) may indicate the severity of the disease.…”
mentioning
confidence: 99%
“…Osteoarthritis (OA) is a degenerative joint disease that is characterized by progressive cartilage destruction and bone changes, accompanied by synovial inflammation [5]. A major objective for OA research is the development of early diagnostic technologies, including those based on genomics, proteomics, and metabolomics [7,15]. Proteomic tools have been used to discover diagnostic or therapeutic biomarkers in OA [2,9].…”
mentioning
confidence: 99%
“…Investigations that involve multiple types of omics data can also aid in the identification of biomarkers, for example, investigations into potential biomarkers in cartilage and chondrocytes are using both transcriptomics and proteomics data (Lewis et al, 2013;Mobasheri, 2012;Williams et al, 2011). Machine learning analysis requires large datasets and so it is essential to consider the number and type of samples that will be generated and their suitability for the application of machine learning.…”
Section: Discussionmentioning
confidence: 98%